Gender Differences in Presentation and Outcomes of Acute Coronary Syndrome: A Multicenter Study - Faiz Ullah,; Atiq Ur Rehman,; Khan, Rahim Dil; Naz, Fareeha; Ahmadyar,; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Gender disparities in acute coronary syndrome (ACS) have been increasingly recognized, with women often experiencing atypical symptoms, delayed care, and poorer outcomes. However, limited local data are available on this subject in Pakistan. Objective: To evaluate gender-based differences in clinical presentation, management, and in-hospital outcomes among patients with ACS in a tertiary care setting. Materials and Method: A prospective observational study was conducted at Hayatabad Medical Complex Peshawar, Pakistan from June, 2024 to November, 2024. A total of 300 ACS patients (180 males and 120 females) were enrolled. Data on demographics, clinical features, treatment modalities, and outcomes were recorded and analyzed using SPSS v26. Results: Female patients were older, had more comorbidities, and presented more frequently with atypical symptoms. They experienced longer delays in hospital presentation, lower rates of reperfusion therapy, and higher rates of complications and in-hospital mortality compared to males. Conclusion: Significant gender disparities exist in ACS presentation and outcomes, warranting gender-sensitive diagnostic and treatment strategies.